THE EFFICIENCY OF ZAKAT, INFAQ, SHADAQAH AND ECONOMIC GROWTH ON THE HUMAN DEVELOPMENT INDEX IN SOUTH SUMATRA PROVINCE: DEA APPROACH - Adawiyah, Robi'atul; Ridho Sahputra, Muhammad (I-Economics, 2025)
Despite steady economic growth and substantial potential in Islamic social finance, South Sumatra continues to face challenges in human capital accumulation, with a Human Development Index (HDI) lagging behind the national average. Addressing this disparity requires moving beyond resource availability to examining the efficiency of resource allocation. This research explores how efficiently the Zakat, Infaq, and Shadaqah (ZIS) funds and economic growth influence the Human Development Index (HDI) in South Sumatra Province. Quantitative methods and secondary data from Central Statistics Agency (BPS) and the National Zakat Agency (BAZNAS) in 2022 are utilized. Each region is assessed for their efficiency in transforming ZIS funds and economic growth (inputs) into HDI (output) using Data Envelopment Analysis (DEA). Among the seventeen districts/cities, this research found significant variations in the efficiency scores, six district/cities like Palembang, Prabumulih, Pagar Alam, Ogan Komering Ulu, South Ogan Komering Ulu and Empat Lawang were determined efficient and other eleven district/cities were inefficient.